Obtaining tissue diagnosis in lung cancer patients with poor performance status and its influence on treatment and survival. (March 2017) - Maclay, John D.; Farley, John M.B.; McCowan, Colin; Tweed, Conor; Milroy, Robert
Abstract: Introduction: 25% of patients with lung cancer have performance status 3 or 4. A pragmatic approach to investigative procedures is often adopted based on the risks and benefits in these patients and whether tissue diagnosis is necessary for anticipated future treatment. This cohort study investigated factors influencing a clinician's decision to pursue a tissue diagnosis in patients with lung cancer and performance status 3 and 4 and to examine the association of tissue diagnosis with subsequent management and survival. Methods: All patients with lung cancer diagnosed in North Glasgow from 2009 to 2012 were prospectively recorded in a registry. We investigated the relationships between achieving a tissue diagnosis, treatment and survival. Results: Of 2493 patients diagnosed with lung cancer, 490 patients (20%) were PS 3 and 122 patients (5%) were PS 4. Tissue diagnosis was attempted in 60% and 35% patients with PS 3 and PS 4 respectively. Younger age, better performance status and having stage 4 disease were independently associated with a diagnostic procedure being performed. Only 5% of patients with poor performance status received treatment conventionally requiring a tissue diagnosis. Age, stage and performance status were independent predictors of mortality. Achieving a tissue diagnosis was not associated with mortality. Receiving treatment requiring tissue diagnosis is associated with survival benefit. Conclusions: The majority of patients with poor fitness undergo a diagnostic procedure which does not influence further treatment or affect survival. However, the cohort of patients who do undergo therapy determined by tissue diagnosis have improved survival. Highlights: Unclear if tissue diagnosis in poor PS lung cancer patients alters outcomes. Tissue diagnosis did not affect treatment or survival in most PS 3 or 4 patients. Those receiving treatment requiring tissue diagnosis had improved survival. Aids decision whether to pursue tissue in PS 3 or 4 patients. Abstract : Currently there is controversy surrounding whether a tissue diagnosis in patients with lung cancer and poor performance status (PS) affects subsequent management and survival. The findings from this study suggest that the majority of patients with PS 3 or 4 undergo a diagnostic procedure which does not affect further treatment or affect survival. However, those poor PS patients who do have treatment requiring tissue diagnosis have improved survival, the majority of whom have small cell lung cancer.